Cavitary lung lesions caused by Pneumocystis jirovecii in setting of common variable immune deficiency. (2020) - Zhang, Zhenmei; Kern, Ryan M.; Joshi, Avni Y.; Iyer, Vivek N.; Escalante, Patricio
Abstract: Pneumocystis pneumonia affects immunocompromised hosts. The typical imaging finding is bilateral diffuse ground glass opacities. Here we presented a case of Pneumocystis causing biopsy-confirmed cavitary lung lesions in a patient with a predominant B cell defect with common variable immune deficiency.